Language Works 4(2) - Andersen, Elisabeth Muth; Dakwar, Julia Rytter; Dalberg, Line; Nguyen, Michael Hai; Sørensen, Søren Sandager; Thøgersen, Jacob (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2019)
Language works and something is worked out through language. This is shown by the four authors of this issue in different ways and by using different methods. The authors address linguistic topics and demonstrate convincingly how linguistic phenomena affect our ability to gain common understanding and perceptions of the social world, and how meaning and action are accomplished through language. The analyses presented are rooted in and related to socially relevant issues, such as second language teaching, diagnosis of depression, gender, and threats as a criminal act.